Humorous Stories in Teaching Reading Comprehension of EFL Students - Yusniati N. Sabata; Lili Ihliyani Kupepe (BABASAL English Education Journal, 2020)
The purpose of this research is to find out the improvement of students’ reading comprehension in eleventh grade at SMA Muhammadiyah Luwuk. To know whether the method is effective or not, the researcher used one-group pre-test and post-test to be applied in eleventh grade. The research conducted eight meetings. The first meeting was for pre-test and sixth meetings were for treatments, and the last meeting was for post-test. As the quantitative method, the researcher analyzed the data using t-test. The results showed that there was significant diffrence on the students’ reading acievement with humorous stories. In the pre-experimental, the students’ mean of pre-test was 36.64 scores, and the students’ mean of post-test was 82.14 scores. The result showed that the t-counted = 8.73 was greater than t-table 1.771. In other words, humorous stories can improve students’ reading comprehension for the eleventh class of senior high school.Keywords: Humorous Stories; Reading Comprehension; Mahasiswa EFL.